Source-matched mobile communications - Wong, W. C (Pentech IEEE Press, 1995)
This book brings you a new approach to designing efficient and robust mobile radio communications links. After introducing the basic concepts of cellular radio and radio links, "Source-Matched Mobile Communications" details the effect of transmission errors on link performance for pulse code modulation (PCM). It describes the interaction between speech coding, channel coding, and modulation for mobile radio links. You'll also find thorough treatment of performance for binary and quadrature amplitude modulation, amplitude weighting of the binary PCM signals, and soft demodulation.